A Virtual Surgical Planning Algorithm for Delayed Maxillomandibular Reconstruction. Issue 4 (April 2019) - Stranix, John T.; Stern, Carrie S.; Rensberger, Michael; Ganly, Ian; Boyle, Jay O.; Allen, Robert J.; Disa, Joseph J.; Mehrara, Babak J.; Garfein, Evan S.; Matros, Evan
Abstract : Background: The absence of a tumor specimen from which to obtain measurements at the time of delayed maxillomandibular reconstruction introduces degrees of uncertainty, creating the need for substantial intraoperative guesswork by the surgeon. Using the virtual surgical planning environment, the size and shape of missing bony elements is determined, effectively "recreating the defect" in advance of the surgery. Three virtual surgical planning techniques assist the reconstructive surgeon: patient-specific modeling, mirroring the normal contralateral side, and scaled normative data. To facilitate delayed reconstruction a hierarchical algorithm using virtual surgical planning techniques was developed. Methods: Delayed maxillomandibular virtual surgical planning reconstructions were identified from 2009 to 2016. Demographics, modeling techniques, and surgical characteristics were analyzed. Results: Sixteen reconstructions were performed for osteoradionecrosis with displacement (50.0 percent) or oncologic defects (37.5 percent). Most patients had prior surgery (81.3 percent) and preoperative radiation therapy (81.3 percent); four had failed prior reconstructions. The following delayed virtual surgical planning techniques were used: patient-specific modeling based on previous imaging (43.8 percent), mirroring normal contralateral anatomy (37.5 percent), and scaled normative data (18.8 percent). Normative and mirrored reconstructions were designed to restore normal anatomy; however, most patient-specific virtual surgical planning designs (71.4 percent) required nonanatomical reconstructions to accommodate soft-tissue limitations and to avoid the need for a second flap. One partial flap loss required a second free flap, and one total flap failure occurred. Hardware exposure was the most common minor complication, followed by infection, dehiscence, and sinus tract formation. Conclusions: Virtual surgical planning has inherent advantages in delayed reconstruction when compared to traditional flap shaping techniques. An algorithmic approach based on available imaging and remaining native anatomy enables accurate reconstructive planning followed by flap transfer without the need for intraoperative guesswork. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.